A psychoacoustic based approach to pavement classification - Freitas, Elisabete F. (2015)
The road traffic noise is one of the major contributors to environmental noise, which can cause considerable impact on public health and quality of life of populations. However, road noise raises several questions because, if on one hand is associated with several health problems and welfare, on the other hand its lack affects the detection of the sound sources, and consequently it constitutes a risk to the safety of road users. Thus, it becomes essential to classify road pavements not only based on acoustic indicators but also based on psychoacoustic indicators. Therefore, this work aims to contribute to pavement classification from the point of view of psychoacoustics. An innovative approach leading to important methodological advantages was done by using the Close proximity Method (CPX) method to acquire tyre-road noise. This work presents the acoustic characterization of five different types of pavement by using three acoustic and psychoacoustic indicators (LAmax, LAeq and Loudness) as a function of speed. Each variable was related to the sound intensity and annoyance evaluation responses of twenty six individuals subjected to the acquired noise. As main results, loudness proved to be a more sensitive variable to vehicle speed and type of pavement than LAmax and LAeq and fits better with individual's responses.